2019
DOI: 10.1017/s1751731119000016
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-oriented action of dietary essential oils to prevent muscle protein oxidation and texture deterioration of farmed rainbow trout

Abstract: Recently, great attention has been directed towards the use of essential oils from aromatic plants as antimicrobials and antioxidant in food matrix. Fish is well known to be a high perishable food. Indeed, fish muscle is susceptible to suffer protein and lipid oxidation during frozen storage, which can lead to the development of softening and undesirable volatile molecules. However, the possible inclusion of essential oils in fish feed for preserving fish flesh quality during storage is still unclear. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Regarding adhesiveness, a slight but significant difference was observed for diet A, producing slightly higher values than diet C. This was also observed in a study carried out in rainbow trout fillets (Santos et al, 2019), in which adhesiveness was also significantly affected by the enrichment of feed with essential oils. These authors observed a particular inhibition of protein oxidation, especially notable in the myofibrillar fraction, and protection of the loss of protein solubility, together preventing flesh changes in adhesiveness.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Regarding adhesiveness, a slight but significant difference was observed for diet A, producing slightly higher values than diet C. This was also observed in a study carried out in rainbow trout fillets (Santos et al, 2019), in which adhesiveness was also significantly affected by the enrichment of feed with essential oils. These authors observed a particular inhibition of protein oxidation, especially notable in the myofibrillar fraction, and protection of the loss of protein solubility, together preventing flesh changes in adhesiveness.…”
Section: Resultssupporting
confidence: 77%
“…Regarding adhesiveness, a slight but significant difference was observed for diet A, producing slightly higher values than diet C. This was also observed in a study carried out in rainbow trout fillets (Santos et al, 2019), in which adhesiveness was also significantly affected by the enrichment of feed with essential oils.…”
Section: Texturesupporting
confidence: 75%
See 1 more Smart Citation
“…In peanut-based milk substitutes, where peanut proteins act as emulsifiers, protein oxidation has a negative impact on emulsion stability . Protein oxidation may lead to increased toughness and decreased juiciness of meat, whereas the consequences on water-holding capacity and drip loss of meat have not yet been fully understood. In the muscle proteins of fish fed with added essential oils, protein oxidation was reduced and the water-holding capacity of the frozen fillets slightly increased . Many of the effects are related to oxidation-induced protein cross-linking, e.g., by cystine or dityrosine.…”
Section: Oxidized Proteins In Food Processing and Human Nutritionmentioning
confidence: 73%
“…Dietary intervention with natural extracts, essential oils, and plant by-products was studied even to enhance meat quality and stability during storage, according to the consumer's demand for "natural animal feeding". A valuable example was recently proposed by Santos and colleagues [10], who found out that an essential oil blend, administrated to rainbow trout, asserted specific protection against lipid and protein oxidation of fish fillets stored at -10 • C for 6 months [10]. Besides, gilthead sea bream (Sparus aurata) shelf life was increased by supplementing the diet with thymol due to the reduction of spoilage and lipid oxidation damages [11].…”
Section: Introductionmentioning
confidence: 99%